Onabotulinumtoxin-A improves health status and urinary symptoms in subjects with refractory overactive bladder: Real-life experience. Issue 4 (November 2018) - Tamburro, Fabiola R; Castellan, Pietro; Neri, Fabio; Berardinelli, Francesco; Bada, Maida; Sountoulides, Petros; Giuliani, Nicola; Finazzi Agrò, Enrico; Schips, Luigi; Cindolo, Luca
Objective: Onabotulinumtoxin-A has been approved for wet overactive bladder refractory to anticholinergics in randomised controlled trials; however, data from real-life practice are scarce. This study was designed to assess the efficacy of intravesical onabotulinumtoxin-A injections, focusing on health status, urinary symptoms and subjective satisfaction. Methods: Data from consecutive patients with overactive bladder-refractory to anticholinergics treated with onabotulinumtoxin-A were prospectively collected and analysed. Standard doses (100–150 U) were used, followed by repeat sessions when clinical benefits diminished. Efficacy and safety of repeat onabotulinumtoxin-A administrations were assessed at 12-week post-injection. Clinical parameters evaluated were: change in the magnitude and frequency of incontinence, urgency and nocturia episodes, change in the number of pads used and procedural complications. Quality of life was evaluated using the 36-Item Short-Form Health Survey, Overactive Bladder Screener and Treatment Benefit Scale questionnaires. Results: Consecutive overactive bladder-refractory to anticholinergics patients ( n  = 22) (median duration of oral therapy: 10 months) were enrolled. No intraoperative complications occurred, but two urinary retention cases were recorded. Forty-five percent of patients (10/22) were re-treated (median duration of perceived benefits: 18 months, range: 8–55 months). The number of urinary incontinence, frequency and nocturia episodes, and pads used went from 3.6, 11.3, 2.7 and 2.4 preoperatively to 1.0, 5.8, 0.7 and 0.7 postoperatively ( p  < 0.005). Quality of life (36-Item Short-Form Health Survey) was significantly improved and symptom scores (Overactive Bladder Screener) were reduced, from 34.5 to 17.1 at week 12 ( p  < 0.05). Eighty-seven percent of patients indicated improvement/great improvement in their condition (Treatment Benefit Scale). Conclusion: Intradetrusor injections of onabotulinumtoxin-A in patients with overactive bladder-refractory to anticholinergics significantly improved health status and urinary symptoms, with high subjective satisfaction.